Metabolic Sensor for Low Intensity Exercise: Insights from AMPKα1 Activation in Skeletal Muscle - Taro Toyoda; Tatsuro Egawa; Tatsuya Hayashi (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Activation of 5'-AMP-activated protein kinase (AMPK) in skeletal muscle is implicated in the multiple health benefits of exercise, including its anti-obesity, anti-diabetic, and anti-aging effects. AMPK consists of three subunits (α, β, and γ), among which the catalytic α subunits (α1 or α2) display distinct activation patterns in response to various stimuli in skeletal muscle. It was widely accepted that α2-containing AMPK (AMPKα2) is more dependent on AMP than α1-containing AMPK (AMPKα1); and that, as muscle energy status decreases, AMPK is activated in the order of AMPKα2 at lower intensities and AMPKα1 at higher intensities. On the other hand, AMPKα1 can be activated in the absence of apparent energy deprivation, indicating that AMPKα1 is a metabolic sensor that responds to low-intensity muscle contraction. Preferential activation of AMPKα1 is found in rat skeletal muscles stimulated ex vivo not only by low-intensity electrical contraction, but also by H2O2 and caffeine, which are well-known metabolic stimulators of skeletal muscle. Although further research is required to verify this hypothesis, AMPKα1 may be one of the signaling intermediaries that lead to the health-promoting effects of low-intensity exercise in daily life.